Endobronchial carcinoid presenting as Focal bronchiectasis in a young woman with systemic lupus erythematosus - Noreen Nasir (Wiley, 2021)
Abstract Non‐resolving pulmonary symptoms in a patient with SLE require evaluation to exclude rare pulmonary lesions, such as carcinoid tumors.